2017
DOI: 10.1021/acs.jafc.6b04658
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Dynamics and Dietary Risk Assessments of Two Neonicotinoid Insecticides during Lonicera japonica Planting, Drying, and Tea Brewing Processes

Abstract: The degradation dynamics and dietary risk assessments of thiamethoxam and thiacloprid during Lonicera japonica planting, drying, and tea brewing processes were systematically investigated using high-performance liquid chromatography. The half-lives of thiamethoxam and thiacloprid were 1.0-4.1 d in the honeysuckle flowers and leaves, with degradation rate constants k ranging from -0.169 to -0.696. The safety interval time was 7 d. The sun- and oven-drying (70 °C) percent digestions were 59.4-81.0% for the resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…However, no significant differences were observed between pesticides or matrices at the same temperature, possibly because the extraction rate of the pesticides is >90% and, thus, no longer sensitive to changes in their water solubility [ 27 ]. The data also reveal that the leaching ratio varies with the type of pesticide, a trend comparable to that observed for neonicotinoids in honeysuckle [ 14 ] and difenoconazole and azoxystrobin in chrysanthemum [ 1 ]. A low leached content was measured, probably due to the influence of the water temperature on the volatilization of the four compounds.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…However, no significant differences were observed between pesticides or matrices at the same temperature, possibly because the extraction rate of the pesticides is >90% and, thus, no longer sensitive to changes in their water solubility [ 27 ]. The data also reveal that the leaching ratio varies with the type of pesticide, a trend comparable to that observed for neonicotinoids in honeysuckle [ 14 ] and difenoconazole and azoxystrobin in chrysanthemum [ 1 ]. A low leached content was measured, probably due to the influence of the water temperature on the volatilization of the four compounds.…”
Section: Resultssupporting
confidence: 67%
“…Whereas most studies have focused on the transfer of pesticides from green tea or black tea [ 13 ] to infusions, only limited information is available on the transfer of pesticide residues from herbal tea. The only previous studies concerning the transfer of difenoconazole and azoxystrobin from chrysanthemum, which was investigated by Xue et al [ 1 ], and that of neonicotinoids from honeysuckle, reported in our previous study [ 14 ]. Unlike green or black tea, herbal tea does not require further processing, such as fermentation [ 15 ], and can, thus, contain higher levels of pesticide residues, with additional health risks for the consumers.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the pesticide residue and time is described by the equation C t = C 0 e − k t , where C t (mg · kg −1 ) is the residue concentration after time t , C 0 (mg · kg −1 ) is the initial residue concentration, and k is the dissipation rate constant (d −1 ). This equation is widely used to assess the levels of pesticides in agriproducts …”
Section: Methodsmentioning
confidence: 99%
“…To end, from the results presented in Table 6 , the presence of UV radiation in sun drying seems to enhance the loss of pesticides during drying, such is the case of quinoxyfen in sun-dried grapes compared to oven-dried [ 214 ], thiamethoxam and thiacloprid in sun-dried honeysuckle compared to shade natural dried [ 215 ], and bifenthrin, which was more affected by sun drying because it is hydrolyzed in the presence of UV rays [ 218 ]…”
Section: Processing On Pesticide Residues Reductionmentioning
confidence: 99%